1996
DOI: 10.1002/ardp.19963290808
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Clozapine Metabolites and Analogues to the Histamine H3 Receptor in Rat Brain Cortex

Abstract: Following up the finding that the non-imidazole drug clozapine shows a considerable histamine H3 receptor antagonistic activity, a series of analogues and metabolites (clozapine-N-oxide, and N-desmethylclozapine) were tested for their affinity towards the H3 receptor using the radiolabelled H3 antagonist [125I]-iodophenpropit. Qualitative structure affinity relationships are derived for the tested compounds. In the clozapine molecule four structurally different moieties may be considered. In comparison with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…We should try another dosage to clarify the effects of CNO on AVP neurons by further study, however, there are some issues to be noticed. Although, CNO is thought to be largely an inactive metabolite 20,21 , some studies reported that administration of CNO caused detectable levels of clozapine which was retro-converted from CNO in the plasma of humans and guinea pigs 22,23 , which may affect animals behavior. Thus, we should pay close attention to the dosage of CNO when conducting behavioural experiments by using DREADDs system.…”
Section: Discussionmentioning
confidence: 99%
“…We should try another dosage to clarify the effects of CNO on AVP neurons by further study, however, there are some issues to be noticed. Although, CNO is thought to be largely an inactive metabolite 20,21 , some studies reported that administration of CNO caused detectable levels of clozapine which was retro-converted from CNO in the plasma of humans and guinea pigs 22,23 , which may affect animals behavior. Thus, we should pay close attention to the dosage of CNO when conducting behavioural experiments by using DREADDs system.…”
Section: Discussionmentioning
confidence: 99%
“…, 1995; Rodrigues et al. , 1995; Alves‐Rodrigues et al. , 1996), subjects who were treated with any of the ATAs or TCAs were included into the ‘ATA/TCA’ groups, while subjects who were treated with typical antipsychotics, mood stabilizers or non‐TCA antidepressants were included in the ‘other medication’ groups.…”
Section: Methodsmentioning
confidence: 99%
“…While clozapine is known to bind to many receptors (Coward, 1992; Schotte et al, 1993; Peters, 2012), the few studies that investigated the pharmacological actions of CNO failed to find any effects. This has led to the consensus that CNO is largely an inactive metabolite (Alves-Rodrigues et al, 1996; Salmi and Ahlenius, 1996; Wong et al, 1996). However, administration of CNO leads to detectable levels of clozapine in the plasma of humans and guinea pigs (Jann et al, 1994; Chang et al, 1998).…”
Section: Introductionmentioning
confidence: 99%